Combined Pyrolysis and Steam Gasification of Hohhot Coal, China - Hong, B.Q.; Wang, X.J.; Zhan, S.P.; Yu, G.S. (Asian Journal of Chemistry, 2013)
The product gas release rate and gas product composition of combined pyrolysis and steam gasification of demineralized Hohhot coal catalyzed by KOH under different temperature and pressure were investigated on a laboratory fixed-bed reactor. The reactions of raw coal, demineralized coal, Ca(OH)2 loaded and Ni(NO3)2 loaded samples were also performed to figure the catalysts effect. It was observed that the catalysts and the mineral in raw coal have less effect on pyrolysis than steam gasification. Potassium hydroxide has the best catalytic performance among the investigated samples. The peak values of H2, CO and CH4 release rates of KOH-added sample during the pyrolysis and steam gasification increase with temperature while the release rate of CO2 reach its maximum value at 750 ºC. Operation pressure has a negative effect on product gas release rates of KOH catalyzed pyrolysis and gasification except for CH4. High temperature was in favour of CO concentration while high pressure was beneficial to CO2 and CH4 contents. Both temperature and pressure had adverse effects on H2 content.